Right frontal stroke : extra-frontal lesions, executive functioning and impulsive behaviour - Scheffer, Morgana (2016)
The aim of this study was to evaluate executive functioning (EF) and impulsiveness in three groups of people aged 30 to 79 years: post-frontal stroke (n = 13) and post-extra-frontal chronic stroke of the right hemisphere (n = 31) and control (n = 38). The years of education varied between the groups was as follows, frontal lesion group: M = 12 (SD = 6.11); extra-frontal lesion group: M = 9.06 (SD = 4.94); and control: M = 9.61 (SD = 4.24) years. The following instruments were used: Behavioural Assessment Dysexecutive Syndrome, Wisconsin Card Sorting Test (WSCT), Barratt Impulsivity Scale, Impulsivity Evaluation Scale, Delay Descounting Task and Go/No-Go Task. We found differences in EF between the extra-frontal lesion group and the control group with respect to cognitive flexibility (p = .018); number of WCST trials (p = .018); WCST perseverative errors (p = .014) and omission by impulsivity errors on the go/no-go task for 250 ms (p = .008) and 1750 ms trials (p = .006). The frontal lesion group made more errors of omission than the control group in the 1750 ms go/no-go trials (p = .006). These results suggest that extra-frontal lesions impair EF by influencing attentional impulsivity.